2020
DOI: 10.1016/j.ejor.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A single-item lot-sizing problem with a by-product and inventory capacities

Abstract: The high pace of waste accumulation in landfills and the depletion of scarce natural resources lead us to seek pathways for converting unavoidable production outputs into useful and high added-value products. In this context, we formalize and propose a model for the single-item lot-sizing problem, which integrates the management of unavoidable production residues classified as by-products. During the production process of a main product, a by-product is generated, stored in a limited capacity and transported w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…To the best of our knowledge, only Sridhar et al (2014) and Suzanne et al (2020b) have treated production planning problems dealing with by-products from an academic point of view. Sridhar et al (2014) studied a generic non-linear production planning problem, where the ratio of undesirable by-products increases monotonically as a convex function of the cumulative production mixture.…”
Section: Joint Production With By-productsmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, only Sridhar et al (2014) and Suzanne et al (2020b) have treated production planning problems dealing with by-products from an academic point of view. Sridhar et al (2014) studied a generic non-linear production planning problem, where the ratio of undesirable by-products increases monotonically as a convex function of the cumulative production mixture.…”
Section: Joint Production With By-productsmentioning
confidence: 99%
“…Sridhar et al (2014) studied a generic non-linear production planning problem, where the ratio of undesirable by-products increases monotonically as a convex function of the cumulative production mixture. Suzanne et al (2020b) proposed a lot-sizing problem, where the by-product is generated in a constant proportion, stored in a limited capacity (constant and time-dependent) and transported to a further destination. They showed that the studied problem is N P -Hard when the capacity is time-dependent, and can be optimally solved in polynomial time when the capacity is constant.…”
Section: Joint Production With By-productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Veinott [3] proved that ZIO policies could be likewise used to derive optimal plans when the cost structure was concave in general. Since then, a significant number of contributions have been published in the literature considering diverse extensions of this simple model (refer to Brahimi et al [4] and Wolsey [5] for more comprehensive surveys and to [6][7][8][9][10] for more recent contributions).…”
Section: Introductionmentioning
confidence: 99%